Production of homeobox A10 gene transgenic pigs by somatic cell nuclear transfer - Qian XIAO; Chang-zhi ZHAO; Rui-yi LIN; Guang-lei LI; Chang-chun LI; Hai-yan WANG; Jing XU; Sheng-song XIE; Mei YU; Shu-hong ZHAO (Journal of Integrative Agriculture, 2019)
Homeobox A10 (Hoxa10) gene is one of the most important candidate genes associated with the reproductive performance of humans and mice. Overexpression of Hoxa10 in mouse endometrium can increase litter size. Moreover, Hoxa10 plays a key role in regulating the embryo implantation of sows. This study aimed to generate transgenic pigs using Hoxa10 via somatic cell nuclear transfer (SCNT). We established seven Hoxa10-transgenic cell lines, and two of the cell lines were selected as nuclear donors for the transfer. A total of 1270 cloned embryos were generated and transferred to five surrogate mothers (Landrace×Yorkshire). Eight cloned male piglets were produced including one with cryptorchidism. Six transgenic piglets grew up healthy and produced 56 offspring. Finally, we obtained six transgenic male pigs and 26 transgenic positive offspring that can be used to further study the regulatory mechanism of Hoxa10 on the reproductive performance of pigs.